2018
DOI: 10.1007/s00167-018-5005-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for residual pivot shift after anterior cruciate ligament reconstruction: data from the MAKS group

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 35 publications
1
51
0
1
Order By: Relevance
“…10-12 Improved control of internal tibial rotation by additional extra-articular tenodesis or ALL reconstruction could protect the ACL graft from excessive stress during the postoperative period and return to sports. 6,10,41,53,54,58…”
mentioning
confidence: 99%
“…10-12 Improved control of internal tibial rotation by additional extra-articular tenodesis or ALL reconstruction could protect the ACL graft from excessive stress during the postoperative period and return to sports. 6,10,41,53,54,58…”
mentioning
confidence: 99%
“…The presence of a high-grade preoperative pivot shift is associated with an increased risk of rerupture after ACL reconstruction and an increased risk of persistent rotatory instability after surgery as compared with a low-grade pivot shift. 11,34,37 Owing to increased knee rotational instability, patients with a grade 3 pivot shift experience poorer clinical outcomes.…”
mentioning
confidence: 99%
“…Several studies have investigated the risk factors for residual instability after ACLR. Ueki et al 31 reported that knee hyperextension and greater preoperative pivot shift under anesthesia were risk factors for residual pivot shift, as evaluated by subjective grading at 1 year postoperatively. Yamamoto et al 35 investigated the relationship between preoperative knee laxity as measured by posterior tibial reduction during the pivot shift using a navigation system and postoperative pivot shift as evaluated by subjective grading at 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 13 Several studies on knee instability have indicated that high-grade pivot shift and knee hyperextension preoperatively are risk factors for postoperative residual instability. 31 With respect to rotation at 30° and 90° of flexion (ie, rotational laxity), a considerable effect of initial knee laxity on postoperative outcomes has been reported. 26 …”
mentioning
confidence: 99%